Analisis Antimullerian Hormon (AMH) di Dalam Serum pada Berbagai Kategori Indeks Masa Tubuh - Didik Rio Pambudi; Ashon Sa’adi; Sudjarwo Sudjarwo (Jurnal Surya Medika (JSM), 2019)
Obesity-related to the result of decreased reproduction. Obese women are more prone to abnormal anovulation and uterine bleeding, endometrial hyperplasia/cancer, infertility, miscarriage, and pregnancy complications, compared to women of normal weight. This study aims to determine the levels of anti-Mullerian hormone (AMH) in the serum at various BMI (body mass index), also to determine the relationship and correlation between obesity and AMH levels in serum. The population in the study were women aged 20 years to 40 years with less BMI, Normal BMI and Obesity BMI. The study subjects were women between the ages of 20 to 40 years with a BMI less than 17-19.9, obesity BMI ≥ 25 and normal BMI 20-25 as controls. Height measurement, weight weighing, and BMI calculation carried out according to the standard and subject to approval. Taking blood samples for the examination of AMH levels carried out by the RSKI laboratory (Infection Special Hospital) Airlangga University. The results of the data processed with SPSS 25 with the Shapiro-Wilk normality test and Mann Whitney statistical analysis for different tests and Spearman analysis for the correlation test. The results of the study found homogeneous samples, there were no significant differences between the AMH levels of the less and obese groups with, p = 0.832 (p> 0.05). AMH levels in BMI were less (0.459 ± 0.112 ng / mL) than obesity BMI (0.432 ± 0.058 ng / mL), so it was concluded that AMH levels did not correlate with less BMI with obesity BMI, with a correlation value (r) = -0.105 (p = 0.643; p> 0.05). The results of this study concluded that body mass index not related and does not correlate with the levels of anti-Mullerian hormone in the serum.